Age, Origin and Tectonothermal Modification of the Falun Pyritic Zn-Pb-Cu-(Au-Ag) Sulphide Deposit, Bergslagen, Sweden: Supplementary data tables ... : Age, Origin and Tectonothermal Modification of the Falun Pyritic Zn-Pb-Cu-(Au-Ag) Sulphide Deposit, Bergslagen, Sweden: Supplementary data tables ... - Kampmann, Tobias (Luleå University of Technology, 2017)
This dataset consists of supplementary data to the article "Age, origin and tectonothermal modification of the Falun pyritic Zn-Pb-Cu-(Au-Ag) sulphide deposit, Bergslagen, Sweden" by Tobias C. Kampmann. The Falun pyritic Zn-Pb-Cu-(Au-Ag) sulphide deposit, situated in the Palaeoproterozoic (1.9–1.8 Ga) Bergslagen lithotectonic unit in the south-western part of the Fennoscandian Shield, is one of the major base and precious metal sulphide deposits in Sweden. Felsic volcanic rocks and limestone hosting the deposit, as well as their hydrothermally altered equivalents and the mineralization, were affected by heterogeneous ductile strain and metamorphism under low-pressure, lower amphibolite-facies conditions during the Svecokarelian orogeny (2.0–1.8 Ga). These processes reworked the mineral assemblages of the original hydrothermal system and the mineralization, and also reshaped the structural geometry of the deposit. A three-dimensional modelling approach has been used in order to evaluate geometric ... : Se engelsk beskrivning för info. Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024. ...